High variability in baseline urinary free cortisol values in patients with Cushing's disease. (15th July 2013) - Petersenn, S.; Newell‐Price, J.; Findling, J. W.; Gu, F.; Maldonado, M.; Sen, K.; Salgado, L. R.; Colao, A.; Biller, B. M. K.
Summary Objective Twenty‐four‐hour urinary free cortisol (UFC) sampling is commonly used to evaluate Cushing's syndrome. Because there are few data on UFC variability in patients with active Cushing's disease, we analysed baseline UFC in a large patient cohort with moderate‐to‐severe Cushing's disease and assessed whether variability correlates with hypercortisolism severity. These data will help clinicians establish the minimum number of UFC samples required to obtain reliable data. Design Observational study (enrolment phase of Phase III study). Methods Patients (n = 152) with persistent/recurrent or de novo Cushing's disease and mean UFC (mUFC) ≥1·5×ULN (normal: 30–145 nmol/24 h) were included. Mean UFC level was calculated from four 24‐h urine samples collected over 2 weeks. Results Over 600 24‐h UFC samples were analysed. The mUFC levels of samples 1 and 2 and samples 3 and 4 were 1000 nmol/24 h (SD 1872) and 940 nmol/24 h (SD 2148), respectively; intrapatient coefficient of variation (CV) was 38% for mUFC. The intrapatient CV using all four samples was 52% (95% CI: 48–56). The intrapatient CV was 51% (95% CI: 44–58) for samples 1 and 2, 49% (95% CI: 43–56) for samples 3 and 4 and 54% (95% CI: 49–59) for samples 1, 2 and 3. Variability in mUFC increased as UFC levels increased. There were no correlations between UFC and clinical features of hypercortisolism. Conclusions There is intrapatient variability of approximately 50% in 24‐h UFC measurements, which is relevant to targets set to estimate any treatment effect. Analysing more than two 24‐h collection periods in individual patients does not result in a relevant decrease in variability. Interestingly, UFC levels did not correlate with hypercortisolism severity.